Value Relevance, Sustainability Reporting Award, and Board Structure: An Influence and Analysis of Value Relevance - Yolanda Florenzcia; Yulius Jogi Christiawan; Juniarti Juniarti (Binus Business Review, 2022)
Research on the relevance of the value of sustainability reporting as measured by the Sustainability Reporting Award (SRA) in Indonesia is still rarely studied. In Indonesia, many go-public companies have not realized the importance of reporting the environment and succeeded in getting the SRA due to the costs incurred in carrying out sustainability reporting activities in accordance with Global Reporting Initiative (GRI). The research examined whether there was value relevance in sustainability reporting information and a role for the board structure in supporting companies to obtain awards or not. The research was conducted with six-year data, with a sample of 29 companies that had received SRA at least once from 2014 to 2019. Then, Ohlson’s model was used to measure the value relevance of accounting information and SR, which was seen through changes in R2. Board structure was proxied with board size, board independence, and board meeting. The test was conducted using SmartPLS. The research results indicate that information on obtaining the SRA does not have the added value relevance, as evidenced by the R2 value. It does not increase and has an insignificant relationship with stock prices. Meanwhile, the board structure that can influence the company in obtaining the SRA is only the independence of the board. The research contributes to showing the value relevance of accounting information and sustainability reporting observed through SRA in Indonesia. Besides that, observing the roles of board structure encourages sustainability reporting of a company in acquiring an SRA.